Recycling of nickel oxide from palm oil mill fuel ash (POMFA) - Ahmad Shahroom, Mohd Shah (2015)
Nickel oxide has been used in lots of industries especially in petrochemical industries, mainly as catalyst in chemical processes due to its unique combination of properties. Nickel oxide also known as heterogeneous catalyst or noble metal catalyst, usually used in hydrogenation reaction. Since nickel oxide demand is extraordinary, production plant for nickel oxide also increase significantly. The downsides of developing a plant is the massive cost required and environmental effect due to disposal of palm oil mill fuel ash (POMFA) from palm oil plant. To solve this issue, other alternative method identified, which is recycling of nickel oxide from palm oil mill fuel ash (POMFA). In Malaysia itself, there are many palm oil plants where the waste from the plant can be used to recover nickel oxide. The objective of this research is to study experimentally the recycling method of nickel oxide from palm oil mill fuel ash and the parameter involve in this experiment (pH value, type of leaching agent and concentration of leaching agent). The recycling of nickel oxide from palm oil mill fuel ash (POMFA) consists of six-step processes which are POMFA characterization, nickel oxide extraction, separation, purification, nickel oxide analysis and lastly yield determination. Once POMFA undergoes those six stages of processes, nickel will be recycled and nickel yield can be determined.